Efficient α‐Helix Induction in a Linear Peptide Chain by N‐Capping with a Bridged‐tricyclic Diproline Analogue1. Issue 36 (19th July 2013) - Hack, Verena; Reuter, Cédric; Opitz, Robert; Schmieder, Peter; Beyermann, Michael; Neudörfl, Jörg‐Martin; Kühne, Ronald; Schmalz, Hans‐Günther
<x xml:space="preserve">Abstract</x> Secondary structure induction: The synthetic tricyclic amino acid ProM‐5, which is formally created by stereoselective introduction of a vinylidene bridge into a di‐proline unit, acts as a powerful scaffold to nucleate α‐helix formation in a linear peptide chain. This might be exploited in the development of new proteomimetics for the modulation of protein interactions.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>